VD_FINDINFO AP / 2011 / 117 vom 7. Oktober 2011 - VD Tribunal cantonal (2011)
ACTION EN MODIFICATION, MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, CONJOINT | 129 CC, 137 al. 2 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)